(untitled) (Revista Inclusiones, 2020)
In order to make effective managerial decisions in the conditions of a dynamic development of a market economy, an enterprise needs an appropriate information support system that reflects the current economic situation objectively. Currently, the topic is relevant, since good information support is not only the key to the success and competitiveness of the company, but it also sometimes acts as a means of survival in a competitive environment.